Indonesia Sharia Bank Merger Process Reviewed from Business Competition Laws - Handyanto, Shahyb; Astuti, Monita Sri; Ajiputra, Kevin Surya (Lex Scientia Law Review, 2021)
Islamic bank entities in Indonesia, namely BNI Syariah, BRI Syariah, and Bank Syariah Mandiri have merged to become Bank Syariah Indonesia. The merger process was effective on February 1, 2021. As we know, the three banks are state-owned, which have significant assets and have a reasonably large market in Indonesia. In connection with business competition law which seeks to create a fair business competition situation in Indonesia, every corporate action, including merger activities, must be notified to the Business Competition Supervision Commission (hereinafter as KPPU) to assess whether monopolistic practices or unfair business competition have occurred or not. The notification is an effort to supervise every business actor in order to carry out activities that do not violate business competition and do not harm other parties. This study aims to examine normatively the merger process carried out based on business competition law in Indonesia. The research uses materials from both regulations, legal principles, doctrine, and sources related to the subject matter. The data obtained were then analyzed for further analysis to produce conclusions. The results showed that the merger process between the three Islamic banks in Indonesia did not violate the business competition law because it did not occur in a position monopoly and the absence of monopolistic practices.